Efficient Adsorption of Methylene Blue Dye Using Ni/Al Layered Double Hydroxide-Graphene Oxide Composite - Amri, Amri; Wibiyan, Sahrul; Wijaya, Alfan; Ahmad, Nur; Mohadi, Risfidian; Lesbani, Aldes (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
To address environmental pollution, we developed Ni/Al layered double hydroxide-graphene oxide (Ni/Al-GO) adsorbent materials for the purpose of eliminating methylene blue (MB) dye pollutants. The adsorption process was explored by examining many experimental factors, including temperature, regeneration/reuse procedure, pH, and time, and their effects on the material. The appropriate model for the isotherm is the Langmuir isotherm. The Ni/Al-GO material achieved a maximum adsorption capacity of 61.35 mg/g for MB dye at a temperature of 60 °C. The thermodynamic characteristics indicate that the adsorption process is both endothermic and spontaneous as the temperature increases. The regeneration method demonstrated that the Ni/Al-GO material has a highly stable structure, enabling it to be utilized for five cycles with a remarkable regeneration rate of 93.49% in the fifth cycle. The pH that yielded the best results for all materials was pH 10, and the kinetic model demonstrated a pseudo second-order behavior. Copyright © 2024 by Authors, Published by MKICS and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).